Risks of cement and rock-cement-metal interface degradation in geological carbon sequestration reservoirs: Mechanisms, influencing factors and mitigation measures - Xinyu Shi; Cheng Zhang; K.K. Gupta; R. Ambat; Min Wu (Carbon Capture Science & Technology)
Geologic carbon sequestration (GCS), a technique for capturing and storing CO2 in deep geologic formations, is considered essential to reduce the alarmingly high carbon emissions causing global warming and climate change. Non-producing oil and gas reservoirs are among the most appealing locations for GCS, though the success of the strategy relies on the long-term integrity of the reservoirs. The degradation of the main reservoir structural and sealing materials including cement and casing steel under the acidic conditions along with potential fluid leakage risks, remains a major concern. This work provides a comprehensive review on the degradation mechanisms affecting cement and the interfaces between cement and casing/formation rock under GCS conditions. The mechanisms and relevant investigation methods for the degradation, both experimental and numerical, are discussed in detail. A special focus is placed on the important influencing factors, especially concerning the exposure conditions inside of the reservoirs, including temperature, pressure, advection conditions, brines as well as contaminants in the stored CO2, etc. In addition, representative mitigation strategies for the degradation of cement and the rock-cement-metal interfaces under GCS conditions are summarised. This review aims to highlight important research progress on the subject and identify critical research gaps and challenges for future studies.